SYNTHESIS OF FERRITE NANOPARTICLES WITH PROTEIN MOLECULES IMMOBILLIZED ON THEIR SURFACES - Tran Hoang Hai; Le Hong Phuc; Doan Thi Kim Dung; Nguyen Thi Le Huyen; Bui Duc Long; Nguyen Tien Thang; Vu Van Do; Nguyen Thi Nhu Quynh; Masanori Abe (Universitas Gadjah Mada, 2008)
The ferrite (a Fe3O4 – gFe2O3 mixed solution) fine particles, 8 nm in size were synthesized from an aqueous solution. Trypsin, a proteolytic enzyme or a protein, was immobilized onto the surfaces of those particles during the synthesis process. The process was performed in the open air at a temperature as low as 4°C and on near-neutral condition of pH = 9, which is compatible with most of the bioactive molecules as well as trypsin. Therefore this technique is advantageous for preparing magnetite particles having biomolecules immobilized on their surfaces, which will be used for biomedical applications utilizing magnetic separation technique.